Violence and order on the Chengdu Plain : the story of a secret brotherhood in rural China, 1939-1949 - Wang, Di, 1956- (Stanford University Press, 2018)
This is the first book-length treatment of the Paoge--a violent secret society located in a rural village near Chengdu, China. The book uses a filicide within the society as a starting point to examine the environment, history, culture, and organization of the Paoge and the structures of local power in 1940s rural Sichuan.